Komunikasi Organisasi Berbasis Kearifan Lokal Kelompok Sadar Wisata dalam Pengelolaan Kampung Adat Cireundeu: Organizational Communication Based on Local Wisdom by the Tourism Awareness Group in the Management of Cireundeu Traditional Village - Diana Simanjuntak; Darmawan Sunarja (Society, 2023)
Visiting tourist villages has become an alternative tourism trend favored by both domestic and international tourists. This trend is driven by tourists’ desire to gain new experiences and discover unique and distinctive natural and cultural attractions. Cireundeu Traditional Village is an increasingly visited destination, especially by students, university students, and academics. The management of these tourist villages is based on community involvement, known as Community-Based Tourism (CBT), where the participation of the local community is essential. This research aims to explore and analyze how the organizational communication of the Pokdarwis (Tourism Awareness Group) is carried out with mentors, fellow administrators, and the community in the context of managing the Cireundeu Traditional Village. The research seeks to identify communication patterns, obstacles, and the effectiveness of the communication strategies implemented. This study uses a qualitative approach with a case study design. Data was collected through participatory observation and in-depth interviews with members of the Pokdarwis, mentors, administrators, and local community members. Data analysis was conducted thematically to identify key patterns and themes in organizational communication based on local wisdom. The results show that Pokdarwis’ organizational communication is mostly acquired autodidactically. They can effectively understand and implement organizational communication functions and flows based on local wisdom. The Pokdarwis can communicate vertically, horizontally, and diagonally with mentors, fellow administrators, and the community. They can also express ideas and views, inform, empathize, and coordinate in the management of the Cireundeu Traditional Village. The organizational communication behavior of the Pokdarwis is based on local wisdom communication traditions, which include the principles of mutual learning, caring, nurturing, and sharing. It also involves relational foundations such as compassion for others, respect for lineage, etiquette, courteous behavior, and self-control.